Buddhists Tourism Promotional Strategy to Nepal (Research Nepal Journal of Development Studies, 2021)
Buddhists Tourism Promotional Strategy to Nepal is the study of Buddhist tourism and its promotional strategy of Nepal. Buddha was born in Nepal, so Nepal must be like Jerusalem and Mecca are for Christians and Muslims of Buddhist, but still, Nepal has difficulties inviting two million overall tourists. Why is it so? Nepal is the country of Buddha; every Buddhist must visit Lumbini Nepal at least once in a lifetime but still status of arrival of Buddhist tourists is considerably low. The main objective of the study is to find out the Buddhists Tourism Promotional Strategy for Nepal. It is a review paper on Buddhist tourism. For this federal, provincial, and local governments have to work effectively with the assurance of good governance on the specified programs.